Concurrent chemoradiotherapy followed by adjuvant chemotherapy versus concurrent chemoradiotherapy alone in locally advanced cervical cancer: A systematic review and meta-analysis - Liu, Haonan; Ma, Xiao; Sun, Chenyu; Wu, Meng; Xu, Zhiyuan; Zhou, Shuang; Yao, Nan; Liu, Suya; Qin, Xiaobing; Han, Zhengxiang (Frontiers in Oncology, 2022)
Objective: To assess the efficacy and safety of adjuvant chemotherapy (ACT) following concurrent chemoradiation (CCRT) in patients with locally advanced cervical cancer (LACC) through a meta-analysis. Methods: MEDLINE, PubMed, Web of Science, EMBASE and the Cochrane Central Register of Controlled Trials from the beginning to May 20, 2022. Randomized controlled trials (RCTs) and observational studies comparing CCRT versus CCRT plus ACT were included. The literature search, quality assessment and data extraction were conducted by 2 reviewers independently. The primary endpoints were 3-year rates of overall survival (OS) and progression-free survival (PFS). Complete response rate, local recurrence, distant metastasis and adverse events were secondary outcomes. The hazard ratios (HR) and relative risk (RR) were pooled. Results: Nine studies with a total of 2,732 patients were included for this meta-analysis, including 1,411 patients in the CCRT group and 1,321 patients in the CCRT plus ACT group. The HR for 3-year rates of OS and PFS of CCRT group compared to CCRT plus ACT group were 0.72 (95%CI=0.44~1.17) and 0.78 (95%CI=0.5~1.75), respectively. There were no significant differences between the two groups in complete response rate (RR=1.06, 95%CI=0.96~1.16). However, local recurrence and distant metastasis were significantly lower in CCRT plus ACT than CCRT (RR=0.63, 95%CI=0.44 ~0.91 and RR=0.64, 95%CI=0.47~0.88). Grade 3-4 acute toxicities were more frequent in CCRT plus ACT group (RR=1.73, 95%CI=1.19~2.52). Conclusion: Although associated with decreased risk of local recurrence and distant metastasis, ACT in patients with LACC did not significantly improve the survival rate and the complete response rate with increasing grade 3-4 acute toxicity. Thus, this adjuvant chemotherapy regimen cannot be recommended for patients with locally advanced cervical cancer.